Can primary palliative care education change life-sustaining treatment intensity of older adults at the end of life? A retrospective study - Qian Liu; Mingzhao Qin; Jian Zhou; Hui Zheng; Weiping Liu; Qi Shen (BMC Palliative Care, 2021)
Abstract Background Palliative care education has been carried out in some hospitals and palliative care has gradually developed in mainland China. However, the clinical research is sparse and whether primary palliative care education influence treatment intensity of dying older adults is still unknown. This study aims to explore the changes to the intensity of end-of-life care in hospitalized older adults before and after the implementation of primary palliative care education. Methods A retrospective study was conducted. Two hundred three decedents were included from Beijing Tongren Hospital’s department of geriatrics between January 1, 2014 to December 31, 2019. Patients were split into two cohorts with regards to the start of palliative care education. Patient demographics and clinical characteristics as well as analgesia use, medical resources use and provision of life-sustaining treatments were compared. We used a chi-square test to compare categorical variables, a t test to compare continuous variables with normal distributions and a Mann–Whitney U test for continuous variables with skewed distributions. Results Of the total participants in the study, 157(77.3%) patients were male. The median age was 88 (interquartile range; Q1-Q3 83–93) and the majority of patients (N = 172, 84.7%) aged 80 years or older. The top 3 causes of death were malignant solid tumor (N = 74, 36.5%), infectious disease (N = 74, 36.5%), and cardiovascular disease (N = 23, 11.3%). Approximately two thirds died of non-cancer diseases. There was no significant difference in age, gender, cause of death and functional status between the two groups (p > 0.05). After primary palliative care education, pain controlling drugs were used more (p < 0.05), fewer patients received electric defibrillation, bag mask ventilation and vasopressors (p < 0.05). There was no change in the length of hospitalization, intensive care admissions, polypharmacy, use of broad-spectrum antibiotics, blood infusions, albumin infusions, nasogastric/nasoenteric tubes, parenteral nutrition, renal replacement and mechanical ventilation (p > 0.05). Conclusions Primary palliative care education may promotes pain controlling drug use and DNR implementation. More efforts should be put on education about symptom assessment, prognostication, advance care planning, code status discussion in order to reduce acute medical care resource use and apply life-sustaining treatment appropriately.